Arab Culture and Civilization - ugli, Nazirov Sherzodbek Rustamsher (International Journal on Human-Computing Studies, 2023)
this article is about the culture of Abrabistan, talking about its civilization in ancient times, as well as the fact that in the 7th century the whole United into a single state, and its culture was even higher.